Analysis of climate types: Main strategies for sustainable decisions in agricultural areas of Carabobo, Venezuela - Orlando, Barlin (2018)
Recently, the agricultural zones of Carabobo present problems with the water available for crops influenced by the fluctuation between Precipitation and Potential Evapotranspiration. It is for this reason that the need arises to analyze the climatic types according to the degree of humidity. The Climatic Hydrological Balance methodology was used for 25 rainfall stations in Carabobo, Venezuela, for a period of common registration (1969 - 1999). The results show that four regions were found where humidity behaves differently, the greatest excesses are to the south of the state and it was found that the climatological stations located north of Carabobo have a greater annual deficit. The most relevant agricultural areas are represented by a water index of (-2.16 to -18.96); which determines a dry sub-humid climate with annual rainfall ranging between 921 mm and 1063 mm. This study generated vital information in those agricultural areas that require additional irrigation or controls with structural drainage works that prevent certain crops sensitive to excess water from being damaged.